PENGARUH DOSIS PUPUK ORGANIK PLUS SEMANGGI DAN SP-36 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vignaradiate L.) VARIETAS VIMA2 - Yogie Handery S.; Nunuk H. (Jurnal Ilmiah Hijau Cendekia, 2017)
The importance of this research is to know the effect of interaction dose of organic fertilizer plus Marsileaand SP-36 on the growth and production of Vigna radiata varieties Vima 2. Organic material from Marsileaorganic fertilizer in soil will improve of soil condition, so the soil aeration will be better. The research was conducted in Rejoagung Village, Kedungwaru District, Tulungagung Regency, March to May 2017. The result of this research were: 1) there is no interaction between organic fertilizer plus doses of Marsilea SP-36 on growth and production of Vigna radiata; 2) there is a real effect on the treatment of organic fertilizer plus Marsilea dose of observation variable of plant height that is at age 28 days after plan is 20,90 (cm), number of leaf is age 42 hst 5,87 (pieces), wet crop weight planting crop 19,85 (gr), dry crop yield 17,12 (gr), no significant effect on stem diameter observation variable; 3) there is a real effect on the treatment of SP-36 fertilizer dose of average observation of plant height that is at age 42 days after plan is 40,05 (cm), number of leaf is age 42 days after plan 5,89 (pieces), harvest number of plant pods 15 , 77, had no significant effect on stem diameter observation variable.